Kreditur paling mendahulu di mata hakim: Sengketa klasik antara pajak, kreditur separatis, dan buruh - Muhasan, Imam; Dwi Lestari, Indah; Simanjuntak, Dumaria (WIM Solusi Prima, 2024)
One of the classical issues faced by Curator in allocating bankrupt debtors assets (bankruptcy boedel) is determining the most preferred creditor between the Tax Authority, Secured Creditors, and Labors. It is so due to those three types of creditors have preferred rights according to the law. This study aims to describe Judges opinion over the preferred rights dispute between the creditors holding the preferred rights. This study is a doctrinal research by using case approach on 25 court decisions with permanent legal force (inkracht van gewijsde) during 1999-2021. This study concluded that there there is no uniformity of opinion among the Judges. There are those who prioritize the Tax Authorities, there are those who prioritize the Secured Creditors, and there are those who allocate the bankruptcy proportionally (pari passu prorata parte). Referring to this result, it is urgent to carry out harmonization between laws on prederred rights. Moreover, Article 95 of Job Creation Law on Employment Cluster jo. Constitutional Court Decision Number 67/PUU-XI/2013 has formulated the new norms regarding the order of priority between creditors.